Improving The Ability of Self-Caring of Leprosy Survivor Through Family Psychoeducation - Muhamad Amang Handaris; Shanti Rosmaharani; Rodiyah Rodiyah (Universitas Muhammadiyah Semarang, 2021)
Leprosy survivor not only suffers physical damage but also suffer psychosocially because of environmental behaviour that causes problems and impacts on their families and sufferers. One way that can be used to overcome this dependence is family psychoeducation. This study aims to determine the effect of family psychoeducation on self-care in leprosy survivor in Jombang. The design of this study was a pre-experimental one-group pre-post test design. The population of the family who had been infected with leprosy were 22 people. The sample size was 22 respondents using total sampling. Data analysis using the Wilcoxon Signed Ranks Test. The results showed that before family psychoeducation 54.5% of self-care was good as many as 12 families but after psychoeducation, the family was 77.3% good as many as 17 families. The Wilcoxon test shows the ρ-value (0.025) <0.05, which means that there is an effect of family psychoeducation on self-care in leprosy survivor. Family psychoeducation has a positive impact on the family, which can improve the ability of the family to carry out self-care independently at home. It can be concluded that family psychoeducation is effective for improving self-care in leprosy survivor. This therapy is expected to be applied so that there is a change in the level of the family's ability to carry out self-care.